COVID-19, Nation-States and Fragile Transnationalism. (February 2022) - Nehring, Daniel; Hu, Yang
In this intervention, we discuss how the COVID-19 pandemic has reconfigured transnational mobilities, connections, and solidarities, which reveals the fragility of transnationalism predicated on cosmopolitan ethics but rooted in nation-level politics. We show that as the pandemic severely disrupted transnational (infra)structures predicated on state-centric transnationalism from above, the survival and well-being of diverse transnationally mobile groups, such as refugees, transnational families, and international students, have been placed under unprecedented threat. In doing so, we reflect on the configurations of transnationalism in sociological understandings of globalisation, in and beyond the context of COVID-19. We advance an urgent call for action to address the consequences of the pandemic for vulnerable people who lead precarious lives in a transnational limbo caught in the gaps between nation-states.